Comparison of Post-Operative Complications of Desarda Non-Mesh Hernia Repair with Lichtenstein Mesh Hernia Repair - Zulfiqar Ali, Shafique-Ur-Rehman, Mehboob Alam Chishti, Harun Javaid Majid, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare Desarda non-mesh hernia repair with Lichtenstein mesh hernia repair regarding postoperative pain, seroma and wound healing. Study Design: Prospective observational study. Place and Duration of Study: Department of General Surgery, Rashid Lateef Medical College/Hosital Lahore from January 2021 to June 2023. Methodology: Sixty patients were enrolled and they were randomly divided into 2 groups. Group A patients were offered Lichenstein repair while group B patients were offered Desarda repair. These two surgical techniques were compared for postoperative pain, seroma formation, and wound infection. Results: Incidence of mild pain as per VAS score in Lichenstein mesh hernia repair group was 60%,46.6% and 10% at 1 POD,7 POD and 14 POD while the incidence of mild pain at these intervals in Desarda non mesh hernia group was 36.6%,13.3% and 0%. The mild form of pain settled with Tablets Panadol. A few of patient needed Diclofenac Sodium to get rule of pain, lesser episodes of pain observed in Desarda group. Incidence of moderate pain as per VAS score in Lichenstein mesh hernia repair group was 23.3%,13.3% and 0% at 1 POD,7 POD and 14 POD while the incidence of moderate pain at these intervals in Desardanon mesh hernia group was 10%,0% and 0%. Incidence of seroma formation in Lichensteinmesh hernia repair at 1, 7 and 14 POD was 10%,6.66% and 0% while incidence of seroma formation in Desarda non-mesh hernia repair at these intervals was 6.66%,6.66% and 0%. Grade 0 wound healing in Lichenstein mesh hernia repair group was (73.3%,90% and 93.3%) vs Desarda non-mesh hernia repair group (66.6%,80%,86.6%) at 1,7 and 14 POD while Grade 1 wound healing in Lichenstein mesh hernia repair group was (26.6%,10% and 10%) vs Desarda non-mesh hernia repair group (16.65,6.6% and 3.3%) at these intervals. Conclusion: The Desarda's technique may be considered as an alternative to mesh-based repairs to avoid long-term mesh-related morbidity for uncomplicated indirect hernias in the younger population Keywords: Post-operative complication, Desarda non-mesh hernia repair, Lichtenstein mesh hernia repair, Postoperative pain, Seroma, Wound healing